INVENTORY MANAGEMENT PRACTICES IN DAPUR HANIF MSME (CAKE BUSINESS): A SINGLE CASE STUDY - Ajeng Purwati Ningtyas (Jurnal Multidisipliner Bharasumba, 2026)
This study examines inventory management practices in Dapur Hanif, a micro scale cake business. (1) Research objective: to describe how inventory is sourced, controlled, and replenished, and to identify the operational implications of these practices. (2) Research method: a qualitative single case study using interviews, observation, and documentation, analyzed through thematic analysis. (3) Research results: Dapur Hanif relies mainly on local markets and nearby baking supply stores, supported by weekly purchasing routines and bulk buying to prevent stockouts. Online channels are used selectively for supporting items such as packaging and certain specialty needs, but not for urgent procurement due to lead-time risk. The owner stockpiles specific materials (whip cream and chocolate-based inputs) to mitigate price volatility and occasional scarcity, creating a trade-off between availability assurance and potential overstock. Stock control remains semi formal, relying on visual checks and experience, while fast turnover and immediate delivery help minimize finished goods waste.